Factors Influecing Continuance Intention of PLN Mobile Applications at PT. PLN (Persero) - Rahmawati, Nadia (JURNAL PENELITIAN PENDIDIKAN, PSIKOLOGI DAN KESEHATAN (J-P3K), 2025)
The company-developed mobile application aims to enhance its services. PLN Mobile is an app created by PT. PLN (Persero). This study analyzes factors influencing continuance intention of the PLN Mobile application, using constructs that shape trust and the UTAUT-2 extended model. Data were collected through online questionnaires from 358 respondents. Partial Least Square Structural Equation Modeling (PLS-SEM) was employed for data analysis. The results indicate that trust, epistemic value, satisfaction, and habit influence continuance intention. This study enhances understanding of determinants of PLN Mobile app continuance intention in the Indonesian state-owned electricity company.